Aplikasi RGB-Colormeter Pada Praktikum Spektrofotometri - Aldio Prima Verguson David; Wilson A R Rombang; Meiske Mamuaja (Chemistry Department, Universitas Negeri Manado, 2021)
The purpose of this study was to determine the application of the RGB-Colormeter application in smartphone-based practicum in online learning. This research was conducted in February-March in the third semester of chemistry education, FMIPA UNIMA. This research was conducted at the Department of Chemistry, FMIPA UNIMA in the 2020/2021 academic year. The research method used is descriptive qualitative. Twenty-two third semester students were selected to be selected as research samples. The data was collected by using a test in the form of essay questions as many as 12 questions about spectrophotometry material. The data collection technique uses practical results. The results of the practicum obtained show that the use of practicum using the RGB-Colormeter application can be used as an alternative method in learning the concept of spectrophotometry during a pandemic and has an effect on students' understanding that is awakened. Based on these results, it can be stated that the practicum method with the RGB-Colormeter application is suitable for use, especially during the pandemic.